Green Hydrogen: Challenges and Opportunities steel production processes at the iron and steel plant (Misurata) - Yuosef A. Adraider; Husein Meshreghi; Ibrahim Imbayah (African Journal of Advanced Pure and Applied Sciences, 2024)
Green energy will be the major issue in this 22-century due to the bad impact of CO2 emissions that come from the burning of fossil fuels. The researchers are playing an important role in finding a variety of ways to get rid of environment-associated issues. Green energy provides the best solution to reduce the influence of greenhouse gases on the environment. Green energy is classified as safe, sustainable, inexpensiveness and zero-emission. One of the best forms of green energy is green hydrogen due to no pollution to the environment. The availability of water resources sunlight and production techniques are great assets for us to produce green hydrogen fuel. This paper proposes the potential option for decarbonization of iron and steel production processes at the iron and steel plant (Misurata), with an emphasis on the use of green hydrogen. It represents hydrogen production processes and the significance of carbon in the iron and steel industry, as well as the effects of switching to green hydrogen in this industrial sector.